Maritime piracy and China's policy options to Southeast Asian waters - Chen, K (World Scientific Publishing, 2015)
Southeast Asia remains one of the worst-hit regions in maritime piracy; pirates adopt new tactics and anti-piracy security governance presents inefficiencies, particularly sovereignty sensitivity in Southeast Asian waters. This article explores the context-sensitive policy options in the foreseeable future. Private security companies could be an alternative solution to maritime piracy for China and the most critical variable would be the China National Security Council.